Retrieving Nicaea :the development and meaning of Trinitarian doctrine the development and meaning of Trinitarian doctrine - Anatolios, Khaled, 1962- (Grand Rapids, Mich. : Baker Academic, 2011)
Khaled Anatolios offers a historically informed theological study of the development of the doctrine of the Trinity, showing its relevance to Christian life and thought today. --from publisher description
Fourth-century trinitarian theology: history and interpretation -- Development of trinitarian doctrine: a model and its application -- Athanasius: the crucified Lord and trinitarian deification -- Gregory of Nyssa: the infinite perfection of trinitarian life -- Augustine's De trinitate: trinitarian contemplation as Christological quest.
Includes bibliographical references and indexes.
Keywords: Trinity -- History of doctrines -- Early church, ca. 30-600.; Dogma, Development of